2016
DOI: 10.1103/physrevd.94.124051
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional black holes in Einsteinian cubic gravity

Abstract: We construct static and spherically symmetric generalizations of the Schwarzschild- and Reissner-Nordstr\"om-(Anti-)de Sitter (RN-(A)dS) black-hole solutions in four-dimensional Einsteinian cubic gravity (ECG). The solutions are determined by a single blackening factor which satisfies a non-linear second-order differential equation. Interestingly, we are able to compute independently the Hawking temperature $T$, the Wald entropy $\mathsf{S}$ and the Abbott-Deser mass $M$ of the solutions analytically as functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
226
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(242 citation statements)
references
References 44 publications
13
226
1
Order By: Relevance
“…In particular, in four dimensions the new term S d reduces to Einsteinian cubic gravity term plus an additional term which vanishes on a VSSS ansatz (1.1). This confirms the claim made in [21] that the Einsteinian cubic gravity is the most general four-dimensional theory with this property.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…In particular, in four dimensions the new term S d reduces to Einsteinian cubic gravity term plus an additional term which vanishes on a VSSS ansatz (1.1). This confirms the claim made in [21] that the Einsteinian cubic gravity is the most general four-dimensional theory with this property.…”
Section: Introductionsupporting
confidence: 78%
“…Note that this condition is not sufficient, as there are theories that are equivalent to Einstein's gravity at the linear level but do not admit single metric function VSSS: for example, Einsteinian cubic gravity in dimensions other than four [20,21]. One way to see that this is not a sufficient condition is to note that imposing the absence of the massive graviton and scalar modes leads to two constraint equations on the c i , however we found that (in d ≥ 5) there are in fact five constraint equations imposed by demanding E t t = E r r .…”
Section: Linearized Field Equationsmentioning
confidence: 99%
See 3 more Smart Citations